Inovasi Dan Tantangan Modal Ventura Syariah Dalam Mendukung Pengembangan Usaha Berkelanjutan - Anwar, Saeful; Sayudin, Sayudin (Fakultas Ekonomi Universitas Gresik, 2023)
Sharia Venture Capital as an alternative financing institution for Muslim entrepreneurs through a systematic approach can develop and mobilize its members to benefit from sharia-based financing opportunities. The purpose of this research is as a financial institution that can provide funding that is the basis for economic growth and development, through venture business capital and capital participation in certain businesses or projects with musharakah or mudharabah contracts depending on the amount of capital deposited. This paper uses a literature study on the Sharia Venture Capital model to see a more appropriate financing model in economic growth and its opportunities and challenges. The result of this study is that the existence of Sharia Venture Capital companies is very urgent in terms of innovation, it is also necessary to pay attention to socialization about Sharia Venture Capital so that Sharia Venture Capital can develop according to the purpose of its establishment. Venture capital in its business runs an investment process starting from the entry of investors by forming a pool of funds, the financing process at the Business Partner Company (PPU) until the withdrawal process of the participation. Venture capital has the characteristics of long-term financial assistance but is not permanent.